PENGEMBANGAN MEDIA LINTASAN “HIGH ROAD-LOW ROAD” PADA MATERI USAHA DAN ENERGI - Lola Pratiwi (Jurnal Pendidikan Fisika dan Sains, 2020)
This research is intended to study the "HR-LR" trajectory media about business and energy material that can be developed and is suitable for use in learning activities. This research uses the Research and Development (R&D) development method and the development model used is 4D. In the 4D Model, the steps of activities carried out at each stage of media development are the stages of definition (definition), design stage, development stage, and development of dissemination (dissemination), but in this study carried out only to the validation stage and not to the dissemination phase (implementation). Learning media on business and energy materials can be developed using the "HR-LR" trajectory. The validation assessment stage is carried out by media experts and material experts, using a questionnaire form validation. The questionnaire used by media experts and material experts each has 4 aspects of Value. The results of media validation carried out by media experts to see the percentage of the feasibility of the "HR-LR" trajectory media on business and energy material as a whole get a percentage of 70% which has the criteria as this medium is suitable for use in media learning activities. While for the results of the overall material validation carried out by the material experts to see the percentage of module eligibility in accordance with the media path "HR-LR" on business material and energy this gets a percentage of 76% who have an opinion about the material in this media both used in learning activities. Keywords : Business and Energy, Friction Style, Media development